Was a government policy able to smooth a fractured agri-food value chain during a COVID-19 lockdown? - Mockshell, Jonathan; Ritter, Thea (Bioversity International and the International Center for Tropical Agriculture, 2022)
Despite widespread use of government policy response instruments to placate impacts that COVID-19 lockdowns had on agri-food value chains, there is limited evidence on their effectiveness and impacts on value chain actors, particularly those in the ‘missing or (hidden) middle.’ 1 To shed on one such policy, we examine whether a fresh fruit and vegetable (FFV) procurement program operated by self-help groups (SHGs) in the state of Odisha, India during the world’s most severe COVID-19 lockdown 2 was able to smooth fractured value chain